Waterlife : Improving Access to Safe Drinking Water in India - Agapitova, Natalia; Navarrete Moreno, Cristina; Barkataky, Rahul (World Bank, Washington, DC, 2017)
With 700 million people residing in rural India over a large and diverse topography, providing access to safe drinking water is a significant challenge. The government has tried, playing a key role in financing and implementing drinking water schemes. However, about 30 percent of urban and 90 percent of rural households still depend completely on untreated surface or groundwater. The health and economic burdens of poor drinking water are enormous. It is estimated that about 21 percent of communicable diseases in India are water-related. In response, Waterlife, a for-profit company based out of Hyderabad, has experimented with an innovative business model—building and operating stand-alone water purification plants in underserved areas of India that would otherwise have no access to safe drinking water. Waterlife partners with local governments to provide the location and money for construction of the plants. Customers pay a small fee to fill up their 20-liter water jars, and this fee is used to pay back the government expenditure and cover ongoing plant maintenance and operations. The Waterlife model builds strong community ownership due to a transparent operating system with responsive customer service; community awareness campaigns on the importance of safe drinking water; locations in convenient public settings; and the training of a local corps of villagers to manage plant operations and maintenance. Impact can be seen in a reduced incidence of waterborne diseases and related medical expenses and improved job opportunities and school attendance for local villages. The expectation is that if continued and expanded, the utilization of Waterlife plants will enhance long-term economic and health development outcomes for disadvantaged and disenfranchised populations in India.